Βιβλιοκρισία:A. WEYL CARR - A. NICOLAIDES (eds.), Asinou across Time: Studies in the Architecture and Murals of the Panagia Phorbiotissa, Cyprus. Dumbarton Oaks Studies, 43. Washington, DC:, 2012. - ΦΩΣΚΟΛΟΥ Bασιλική (Byzantina Symmeikta, 2015)
Bιβλιοκρισία: Annemarie Weyl Carr -Andréas Nicolaïdès (eds.), Asinou across Time: Studies in the Architecture and Murals of the Panagia Phorbiotissa, Cyprus. Dumbarton Oaks Studies, 43. Washington, DC: Dumbarton Oaks Research Library and Collection, 2012. Pp. xii, 431. ISBN 9780884023494.